A systematic review protocol of injuries and illness across all the competitive cycling disciplines, including track cycling, mountain biking, road cycling, time trial, cyclocross, gravel cycling, BMX freestyle, BMX racing, e-sport, para-cycling and artistic cycling - Fallon, Thomas; Heron, Neil (Frontiers in Sports and Active Living, 2024)
• There is a lack of injury and illness epidemiology research within competitive cycling.• In epidemiological studies completed to date, there is a lack of methodology homogeneity around the definitions of injury and illness and reporting standards. • The Union Cycliste Internationale (UCI) Agenda 2030 acknowledges the lack of epidemiological research within cycling. It aims to "promote and support research in cycling epidemiology and medicine, especially for the benefit of lesser-known disciplines".• This manuscript outlines a protocol that future studies can use to carry out a multidiscipline systematic review of injuries and illness in competitive cycling.• This protocol can be repeated over time to give an up-to-date understanding of the prevalence of injury and illness within cycling across all competitive disciplines. • Upon completion, studies that follow this proposed protocol will formally highlight the shortcomings in research and provide direction for further research within cycling.